2022
DOI: 10.3390/cli10070107
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological and Meteorological Variability in the Volga River Basin under Global Warming by 1.5 and 2 Degrees

Abstract: The idea of the research to assess the impact of 1.5 °C and 2 °C global warming in the 21st century on the runoff formation in the Volga basin corresponds to the Paris agreement on climate change 2016 with the main goal to keep the global air temperature rise to below 2 °C relative to the pre-industrial level and to take measures to limit warming to 1.5 °C by the end of the 21st century. The purpose of this study was to obtain physically based results of changes in the water regime of the Volga basin rivers un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…Evidently, the naturalization procedure for water flow should include a set of methods, including hydrological models that describe hydrological processes with various level of detail (Motovilov et al 1999;Kalugin 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Evidently, the naturalization procedure for water flow should include a set of methods, including hydrological models that describe hydrological processes with various level of detail (Motovilov et al 1999;Kalugin 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The VRB is mainly affected by the continental climate, and is cold and snowy in winters and warm and humid in summers. The upper, middle and right bank of the lower reaches have a forest climate, the left bank of the lower reaches has a steppe climate and semi-desert climate, and the Caspian Sea lowland has a desert climate [40]. Annual PPT is 635 mm in the northwest and 305 mm in the southeast.…”
Section: Study Areasmentioning
confidence: 99%
“…The main sources of river recharge in the basin are PPT, GW, glacier melt, snow melt and lake water [62]. Since the VRB is located in the middle and high latitude region, its water source comes from snowmelt (60%), GW (30%) and PPT (10%) [40]. Figure 12a shows that the correlations between SWE, GW and the FPI are much stronger than the ones between PPT and the FPI.…”
Section: Path Of Flood Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Kalugin (2022) used the precipitation and temperature outputs of two CMIP5-GCMs, including GFDL-ESM2M and MIROC5, over the Volga River basin to assess climate change impacts on the Volga River runoff in the 21st century. Kalugin (2022) reported that in the projected global warming scenarios of 1.5°C and 2°C by 2045 and 2064, the Volga basin could experience mean annual air temperature increases of 2.5 °C and 3.4 °C, respectively. Annual precipitation in the Volga basin increases by 8% at 1.5 °C global warming and averages 11% at 2 °C global warming.…”
Section: Introductionmentioning
confidence: 99%